1987
DOI: 10.2337/diacare.10.2.180
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Diabetes Mellitus in Rural Saudi Arabia

Abstract: Several studies have clearly shown the impact of modernization on the prevalence of diabetes mellitus in susceptible communities. Saudi Arabia has faced a rapid development program over the last two decades. In a recent study, we found a high prevalence of diabetes mellitus in urban Saudi Arabia. A total of 5222 rural subjects of both sexes were involved in a study of the prevalence of diabetes mellitus in the western region of Saudi Arabia. Random capillary blood glucose, body weight and height, and income we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
55
3

Year Published

1989
1989
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(67 citation statements)
references
References 8 publications
9
55
3
Order By: Relevance
“…A considerably lower frequency of hyperglycemia was encountered in Najran in the Southwestern Province, and the majority of the cases were in the age group 40 years or more. This was in agreement with the results of Fatani and coworkers 7,8 and Bacchus and coworkers 5 in western and central Saudi Arabia, respectively. Riyadh results were based mainly on samples collected from blood donors who had the lowest frequency (i.e., 1.4%) and university students in the age range 18 to 30 years who had an overall frequency of about 6.3%.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…A considerably lower frequency of hyperglycemia was encountered in Najran in the Southwestern Province, and the majority of the cases were in the age group 40 years or more. This was in agreement with the results of Fatani and coworkers 7,8 and Bacchus and coworkers 5 in western and central Saudi Arabia, respectively. Riyadh results were based mainly on samples collected from blood donors who had the lowest frequency (i.e., 1.4%) and university students in the age range 18 to 30 years who had an overall frequency of about 6.3%.…”
Section: Discussionsupporting
confidence: 93%
“…In a survey of 1018 patients referred to King Abdulaziz Hospital in Jeddah, 30% of the patients had diabetes mellitus. 6 In a comprehensive investigation on the population of the Western Region of Saudi Arabia, a prevalence of 4.95% and 4.3% was encountered in urban 7 andrural 8 populations,respectively. Otherstudies have shown that the majority of Saudi diabetics suffer from noninsulin-dependent (type II) diabetes, 9,10 though type I diabetes 11 and type II diabetes of the young (maturity-onset diabetes of the young) 12 have been reported in isolated cases.…”
Section: Accepted For Publication 4 December 1988mentioning
confidence: 99%
“…Of relevance is the higher frequency of diabetes encountered in the Riyadh population compared to the findings of two studies from the Western region. 10,11 This may be due to differences in the socioeconomic status in a majority of the population in Riyadh. Riyadh is the capital of the country and the impact of modernization is higher here than in other parts of the country.…”
Section: Discussionmentioning
confidence: 99%
“…7 The prevalence of ICAs was found to be low in non-Caucasian diabetic patients from Nigeria 8 and Pima Indians in Arizona, U.S. , 9 indicating the type 2 form. Saudi Arabia has a high incidence of diabetes among its population 10,11 but the prevalence of ICA has not been explored. This study examined the frequencies of ICA as well as CF-ICA and thyroid, stomach, and antinuclear antibodies in Saudi patients with newly diagnosed diabetes.…”
Section: Osmentioning
confidence: 99%